AB0183 Isolation and characterization of circulating fibrocytes from systemic sclerosis patients: an vitro investigation. (15th June 2017) - Brizzolara, R; Montagna, P; Soldano, S; Trombetta, AC; Contini, P; Smith, V; Ruaro, B; Sulli, A; Cutolo, M
Abstract : Background: In physiological and pathological conditions, such as in tissue repair and in fibrosing diseases (i.e. systemic sclerosis, SSc), the importance of circulating fibrocytes relies on the capacity of such cells to migrate into scleroderma-affected tissues (through CXCR4/CXCL12 interaction) and to differentiate into fibroblasts/myofibroblasts, inducing fibrosis (through matrix protein deposition) (or both) [1–3]. In addition, fibrocytes seem to exert immunomodulatory effects, expressing class II major histocompatability complex molecules (HLA-DP, -DQ, and -DR) [4]. Objectives: To isolate fibrocytes from Circulating Progenitor Cells (CPCs - peripheral blood mononuclear cells PBMCs) of SSc patients and healthy subjects and to identify them by fluorescence-activated cell sorter analysis (FACS), using their specific markers: the leukocyte common antigen CD45, collagen I (COL I), the chemokine receptor CXCR4 and HLA-DR [2]. Methods: Samples were collected, at basal time (t0), from 11 SSc patients, affected by SSc (treated only with different vasodilator drugs) and 5 healthy subjects (CNTs). PBMCs, isolated from 9 among the SSc patients, were cultured on fibronectin-coated plates [5]. The non-adherent cells were removed and after 8 days (t8) of culture (standardized time), the adherent spindle shaped cells were lifted through incubation in 0.05% EDTA (ice-cold). Fibrocyte identification (at both t0, t8), was performed by FACS, using anti-CD45, anti-COL I, anti-CXCR4 and anti-HLA-DR monoclonal antibodies. Results: FACS analysis revealed that, at basal time (t0), among the CD45+ cells, the percentage of fibrocytes, identified as triple positive (CD45+, COL I+, CXCR4+) was 1.0±1.2% in SSc patients and 0.4±0.3% in healthy subjects (CNTs). In addition, the HLA-DR expression on fibrocytes in both SSc patients and CNTs showed low values (22.1±21.1% and 7.1±6.1%, respectively). After 8 days (t8) of culture, fibrocytes presented adherent and spindle shaped morphology. Interestingly, the FACS analysis at t8 of culture, demonstrated that the percentage of SSc fibrocytes CD45+, COL I+, CXCR4+ increased up to 52.8±27.1%, compared to basal time (t0), as well as strongly increasing the HLA-DR+ expression (90.1±22.7%). Conclusions: Fibrocytes isolated from CPCs of SSc patients were confirmed to express CD45, COL I and CXCR4 molecules, but in very low percentage at the beginning. Already after 8 days of culture in proper conditions, the percentage of differentiated fibrocytes (CD45+, COL I+ and CXCR4+) from SSc patients, increased up to 50 times and the HLA-DR expression increased up to 68%. Additional markers of progressive fibrocyte differentiation are now under test to further characterize the fibrocytes phenotype(s) of SSc patients vs healthy controls. References: Chesney J et al. Proc. Natl. Acad. Sci. 1997; 94:6307–6312. Bucala R. Mol Med 2015;21:S3–S5. Brunasso A.M. et al. F1000Research 2016;5:723. Blakaj and Bucala. Fibrogenesis & Tissue Repair 2012;5:S6. Pilling D et al. J Immunol Methods 2009; 351:62–70. Disclosure of Interest: None declared